Influence of gamma radiation on nutritional quality and shelf life of fresh red chilies (Capsicum annuum) - Kaleem, Afshan; Shafique, Ramish; Iqtedar, Mehwish; Abdullah, Roheena; Saleem, Faiza; Aftab, Mahwish; Naz, Shagufta; Sharif, Saima; Alyas, Saeeda (Progress in Nutrition, 2021)
The aim of this work was to optimize the best suitable dose that effectively removes microbes, enhances the shelf life and has least negative effect on nutritional value of fresh red chili. The samples were packed in polyethylene bags and irradiated with selected doses (5, 6 and 7.5 kGy) using gamma radiation. Along with control sample, irradiated samples were stored at their storage temperature 4-7 °C for 15 days and were analyzed weekly. Impact of gamma irradiation on microbial load, sensory attributes like, color, texture, appearance, pungency and overall acceptability as well as on proximate composition was evaluated. 7.5 kGy was proven to be most effective dose as microbial load remained minimal and their nutritional value did not change significantly of fresh red chili, which suggest that gamma irradiation of 7.5 kGy can be used for enhancement of shelf life.